2011
DOI: 10.3389/fmicb.2011.00189
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Function of the Outer Membrane Channel TolC in Multidrug Resistance and Physiology of Enterobacteria

Abstract: TolC is an archetypal member of the outer membrane efflux protein (OEP) family. These proteins are involved in export of small molecules and toxins across the outer membrane of Gram-negative bacteria. Genomes of some bacteria such as Pseudomonas species contain multiple copies of OEPs. In contrast, enterobacteria contain a single tolC gene, the product of which functions with multiple transporters. Inactivation of tolC has a major impact on enterobacterial physiology and virulence. Recent studies suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
203
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(211 citation statements)
references
References 129 publications
8
203
0
Order By: Relevance
“…However, it is also possible that hopanoids interact directly with certain proteins, modulating their action. There are diverse OM efflux proteins that interact with different types of transport systems to facilitate cellular efflux (52)(53)(54)(55). The activity of an OM efflux protein might potentially be impaired by altered diffusivity or defective gating associated with a change in membrane order (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that hopanoids interact directly with certain proteins, modulating their action. There are diverse OM efflux proteins that interact with different types of transport systems to facilitate cellular efflux (52)(53)(54)(55). The activity of an OM efflux protein might potentially be impaired by altered diffusivity or defective gating associated with a change in membrane order (52).…”
Section: Discussionmentioning
confidence: 99%
“…There are diverse OM efflux proteins that interact with different types of transport systems to facilitate cellular efflux (52)(53)(54)(55). The activity of an OM efflux protein might potentially be impaired by altered diffusivity or defective gating associated with a change in membrane order (52). For instance, it has been shown that the substrate affinity of proteins and receptors in the eukaryotic plasma membrane is modulated by cholesterol ordering (35,56).…”
Section: Discussionmentioning
confidence: 99%
“…The cooperation between AcrB and TolC is mediated by the periplasmic protein AcrA (43 kDa) 9 and the activity of the AcrAB efflux pump is under the control of stress response genes 8 . The role of TolC in enterobacteria physiology is very broad and inactivation of tolC gene affects the cell adaptation to adverse environments 10 . Toxic organic compounds that enter inside of the cell cause sometimes DNA damage which activates the SOS response in Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the crystal structure of CusB in complex with CusA, which are the components of an RND-type tripartite pump CusB-CusACusC, revealed that the MFP CusB assumes a funnel-like hexameric assembly upon interaction with the RND-type transporter (19). Nevertheless, the assembly mechanism for the RND-type efflux pump has been considered to remain unclear (16).…”
mentioning
confidence: 99%